Novel signal processing method for vital sign monitoring using FMCW radar. (March 2017) - He, Mi; Nian, Yongjian; Gong, Yushun
Highlights: Multiple vital signal monitoring can by realized by the FMCW wide-band radar. A vital signal separation method is proposed based on a double parameter LMS filter. The proposed separation method can obtain accurate respiration and heartbeat signals. The proposed method can achieve precise estimation under a low signal to noise ratio. Abstract: Purpose: To prove that frequency modulated continuous wave (FMCW) radar can be applied for continuous and timely monitoring of vital signs for multi-human targets. Methods: The chest-wall periodic vibration information resulting from respiration and heartbeat is modulated in the reflected electromagnetic wave of radar from the surface of human bodies or tissue boundaries. The range and vibration information of multi-targets is acquired by a Fourier transform and demodulation processing. To further extract the respiration and heartbeat signals from the mixed vibration phase signal when the respiration signal has several significant harmonics and variant frequencies, a novel recovery and separation method based on a double parameter least mean square (LMS) filter is developed. Results: The FMCW wide-band radar is capable of multiple vital signal monitoring and subject localization under a low signal to noise ratio (SNR). Compared with the bandpass filtering (BPF) method and wavelet transform (WT) method, the proposed method based on a double parameter LMS filter can obtain more accurate respiration and heartbeat signals. Conclusions: The FMCW wide-band radar is a reliable, robust, and harmless tool for continuous and timely monitoring of cardiac and respiratory rates for multi-human targets, which has a potential to be applied in wards or home healthcare.